The Indirect Impact of Global Financial Crisis on Indonesia Exports to Japan - , ANNISA CAESARA HIDAYATI; , Drs. Ahmad Jamli, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
As a big developing country, Indonesia always tries to integrate the world economy and as one part of the world financial system. Indonesia as an export country which highly dependent on the international market, the global financial crisis has also affected the Indonesiaâs economy and trade market. This paper examines the effects of external shock of global financial crisis to Japan on Indonesia exports with a focus on the total export values of Indonesia to its major export destinations, Japan, using the Error Correction Model for the period 2000-2013. The estimation results show that the external shock of global financial crisis to Japan has no significant influence in Indonesia exports due to the effects of financial crisis.